Micromorphology of epicuticular waxes in genus Mimosa (Fabaceae) - Grohar, Mariana Cecilia (2023)
Epicuticular waxes crystallize on the foliar surface with different morphologies, which can be taxonomically relevant features in many taxa. Their morphological analysis was based on scanning electron microscopy (SEM) images on herbarium specimens of selected sections of Mimosa. The present work is the first detailed description and classification of the epidermal micromorphology in the genus Mimosa, focusing on section Calothamnos and Mimosa series Mimosa, subseries Dolentes and Brevipedes. We also describe different wax crystallization morphologies present in these taxa, identifying three different crystallization types: film, plates, and platelets. Novel epidermal micromorphologies have been described, such as papillae in M. lepidorepens. Results allow grouping taxa of the studied sections, contributing to clarifying their taxonomy. SEM images of epicuticular waxes and leaf surfaces could be a new tool for performing a new taxonomic treatment of section Mimosa subser. Dolentes and subser. Brevipedes, and section Calothamnos.